Analysis of Differences in Productivity and Income from Rice Farming Between Subsidized and Non-Subsidized Fertilizer Users in Ahuhu Village, Meluhu Subdistrict, Konawe Regency - Pratiwi, Niken Ayu; Fyka, Samsul Alam; Sudarmo, Hadi (International journal of technology and education research, 2026)
This study aims to determine: (1) the level of lowland rice productivity of fertilizer subsidy recipient farmers, (2) the level of income of lowland rice farming of fertilizer subsidy recipient farmers, and (3) the differences in productivity and income between fertilizer subsidy recipient farmers and non-subsidy farmers in Ahuhu Village, Meluhu Subdistrict, Konawe Regency, Southeast Sulawesi Province. The population of this study consisted of all lowland rice farmers in Ahuhu Village, totaling 107 farmers. This research employed a census method, in which the entire population was used as the sample. Data were analyzed using productivity and income formulas, and the mean difference test was conducted using SPSS version 26. The results of this study indicate that the fertilizer subsidy policy has not resulted in a statistically significant difference in the productivity of lowland rice farming. However, fertilizer subsidies have proven to have a positive impact on the income of farmers who receive fertilizer subsidies